2017
DOI: 10.1007/s10549-017-4162-3
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer-specific survival in patients with lymph node-positive hormone receptor-positive invasive breast cancer and Oncotype DX Recurrence Score results in the SEER database

Abstract: Overall, 5-year BCSS is excellent for patients with RS < 18 and micrometastases, one or two positive lymph nodes, and worsens with additionally involved lymph nodes. Further analyses should account for treatment variables, and longitudinal updates will be important to better characterize utilization of Oncotype DX testing and long-term survival outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 17 publications
4
88
0
Order By: Relevance
“…Molecular assays (eg, a loss of heterozygosity) are more reliable approaches for showing clonal relationships between original tumors and ipsilateral IBCs and for distinguishing genetically related recurrences from genetically distinct new primaries. Using commonly used definitions of intermediate (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and high recurrence risks (≥31) generated a similar result. The 21-gene recurrence score is an assay based on reverse transcription-polymerase chain reaction that is currently applied to early-stage, ER+ IBC to assess the prognosis and the likely benefit from chemotherapy in addition to endocrine therapy.…”
Section: Discussionmentioning
confidence: 62%
“…Molecular assays (eg, a loss of heterozygosity) are more reliable approaches for showing clonal relationships between original tumors and ipsilateral IBCs and for distinguishing genetically related recurrences from genetically distinct new primaries. Using commonly used definitions of intermediate (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and high recurrence risks (≥31) generated a similar result. The 21-gene recurrence score is an assay based on reverse transcription-polymerase chain reaction that is currently applied to early-stage, ER+ IBC to assess the prognosis and the likely benefit from chemotherapy in addition to endocrine therapy.…”
Section: Discussionmentioning
confidence: 62%
“…The identification of patients with high clinical risk and low genomic score with at least a 92.5% chance of being free of distant metastasis without chemotherapy at 5 years was demonstrated using the Mammaprint assay in the MINDACT trial . Prospective outcomes in >60,000 patients (including both clinical and epidemiological data) treated based on 21‐gene assay results have shown that patients within the low RS group (RS < 18) have excellent outcomes without chemotherapy . The prognostic power of the RS was validated in an endocrine‐treated NSABP B14 cohort, in the Kaiser Permanante, JBCRG, SWOG 8814 and in the transATAC studies .…”
Section: Introductionmentioning
confidence: 99%
“…It was seen that CT was beneficial in distinguishing nodepositive patients who would benefit from CT (Predictor of likelihood of chemotherapy benefit in ER+ Node positive disease). Its prospective validation in the node-positive patients was demonstrated in the West German Study Group Plan B Randomized Phase-3 study, the Clalit Registry study conducted in Israel and the SEER real-life observational study (31)(32)(33). In all these studies, the 5-year survival rate of patients in the low risk group is >95%.…”
Section: -Gene Recurrence Score Assay (Oncotype Dx) (Table 3)mentioning
confidence: 98%